Perceived Types, Causes, and Consequences of Financial Exploitation: Narratives From Older Adults. (10th January 2021) - Nguyen, Annie L; Mosqueda, Laura; Windisch, Nikki; Weissberger, Gali; Axelrod, Jenna; Han, S Duke
Abstract: Objectives: The goal of this study was to investigate the perception of financial exploitation and its causes and consequences by older adults who have firsthand experience of being exploited. Method: Thirty-one cognitively healthy older adult participants aged 50 or older were drawn from the Finance, Cognition, and Health in Elders Study. In-depth, one-on-one interviews were conducted. Interview transcripts were analyzed using an iterative, data-driven, thematic coding scheme and emergent themes were summarized. Results: Categories of financial exploitation included (a) investment fraud, (b) wage theft/money owed, (c) consumer fraud, (d) imposter schemes, and (e) manipulation by a trusted person. Themes emerged around perceived causes: (a) element of trust, (b) promise of financial security, (c) lack of experience or awareness, (d) decision-making, and (e) interpersonal dynamics. Perceived consequences included negative and positive impacts around (a) finances, (b) financial/consumer behaviors (c) relationships and trust, (d) emotional impact, and (e) future outlook. Discussion: These narratives provide important insights into perceived financial exploitation experiences.